Symbolic Violence in Learning Discourse - Ulfah, Ulfah (Universitas Negeri Makassar, 2013)
This study aims to describe the form of symbolic violence and sensorisasi euphemization mechanisms. This type of research is classified as critical discourse analysis (AWK) model of Bourdieu. Data sourced from verbal communication teacher-student, student-teachers, and students in learning at SMK Negeri 3 Palu. Data collected through observation, recording, and recording. The results showed that there are a variety of mechanisms and sensorisasi euphemization represented in the discourse of learning